Genome-wide analysis of Circular RNAs reveals circCHRNG regulates sheep myoblast proliferation via miR-133/SRF and MEF2A Axis - Yue Liu; Qian Chen; Jingjing Bao; Yabin Pu; Han Jianlin; Huijing Zhao (MDPI, 2022)
As relatively new members of the non-coding RNA family, circRNAs play important roles in a variety of biological processes. However, the temporal expression pattern and the function of circRNAs during sheep skeletal muscle development remains unclear. This study aimed to identify circRNAs related to sheep skeletal muscle development and explore their roles in myoblast proliferation. The circRNA expression profiles of longissimus dorsi of sheep from F90, L30, and A3Y were obtained by the RNA-seq method. The function and mechanisms of the novel circCHRNG in muscle satellite cell proliferation were explored using CCK-8 assay, Western blot, qPCR, and dual-luciferase reporter assay. We identified 12,375 circRNAs, including 476, 133, and 233 DEcircRNAs found among three comparative groups. KEGG results showed that DEcircRNAs were enriched in muscle contraction, the regulation of cell proliferation, and the AMPK, insulin, and PI3K-Akt signaling pathways. Notably, a novel circRNA, termed circRNA CHRNG, acts as a miR-133 sponge to promote skeletal muscle satellite cell proliferation. Our study provides a systematic description of circRNAs of ovine skeletal muscle across fetal, lamb, and adult stages. GO and KEGG analyses showed that DEcircRNAs were enriched in multiple pathways associated with muscle development, such as the PI3K-Akt and AMPK signaling pathways. In addition, we propose that circCHRNG acts as a miR-133 sponge to upregulate the expression levels of SRF and MEF2A, thereby promoting myoblast proliferation.